THE IMPACT OF E-PROCUREMENT ON BUSINESS PERFORMANCE. A CASE STUDY OF JESA DIARY FARM - TALEMWA JOSHUA (UCU, 2024)
The study aimed to assess the Impact of E-Procurement on Business Performance. A case study was conducted with Jesa Dairy Farm in Wakiso district, central Uganda. A survey method was adopted using a validated structured questionnaire. Data was collected on: socio – demographic characteristics of respondent, the extent to which e-procurement influences key performance indicators, challenges and barriers faced during the implementation and optimization of e-procurement systems and factors that influence the successful adoption and utilization of e-procurement systems. Data was analysed in a descriptive way.The research findings indicate that e-procurement plays a significant role in reducing costs, streamlining procurement cycles, and improving compliance and transparency. However, several challenges emerged, notably technical issues, inadequate training, and high implementation costs, with insufficient training identified as the most pressing concern. The study emphasizes the importance of strong support from top management and a solid technological foundation for successful adoption. While engaging suppliers is crucial, it was rated slightly lower in importance than other factors. To address these challenges, the dissertation recommends investing in technical support, implementing comprehensive training programs, and actively involving suppliers to enhance cooperation and system effectiveness. Overall, this research provides practical insights for optimizing e-procurement practices in agricultural settings, highlighting the need for strategic management and ongoing improvements.